The costs of caregivers for children with disabilities that participate in centre-based and home-based community-based rehabilitation (CBR) programmes in the East Coast of Malaysia. - Hasan, Haliza; Syed Junid, Syed Mohamed Al Junid; Muhammad Nur, Amrizal (International Islamic University Malaysia, 2019)
Rehabilitation for disabled children requires long-term programmes which are expensive to the family. This study aimed to estimate the cost incurred by caregivers’ children with disabilities from Pahang, Terengganu and Kelantan participating in Community-Based ehabilitation (CBR) (CentreBased and Home-Based) and cost of seeking alternative rehabilitation. Cost analysis using the Activity-Based Costing (ABC) method was used to estimate twelve-months’ expenditure in 2014 institutional year on 297 caregivers of children with disability, aged 0 to 18 years who attended CBR. Data were collected using a self-administered costing questionnaire and presented in median (IQR). Results showed that the median direct and indirect costs, excluding medications and alternative care were nearly four times as high in Home-Based compared to Centre-Based (RM2, 376 (11,228) vs. RM608 (739) (p = <0.001). Both groups of caregivers spent a significant amount of resources on alternative rehabilitation. The high costs incurred for alternative rehabilitation is a major economic burden to the family.